Sink node mobility in covering monitoring area for data collection in WSNs - Kamat, Maznah; Ismail, Abdul Samad; Olariu, Stephan; Maarof, Mohd. Azaini; Salleh, Shaharuddin (2007)
Communication in Wireless Sensor Networks (WSNs) plays an important role in relaying data collected by sensor nodes to reach an intended destination (a sink or an in-situ user). However, communication is the dominant energy consumer that must be minimi~ed in order to sustain network lifetime. Several mechanisms that exploited mobile sink have been devised to reduce sensor's communication, however, they do not consider coverage area problem. We proposed a design ofa simple mobility pat/ern ofa sink node in covering a monitoring area of interest in collecting data for a specific mission by traversing the entire area from an ent,y point and finish at an exit point on the square grid. By employing simultaneous equation technique, the square roots oflinear and non-linear equations are calculated which will be used to change the traversal direction ofthe mobile sink. In addition, two types of traversals are compared - the horizontal and vertical traversals.